Visiting of Carpenter Bees Xylocopa latipes Drury to The Bean Crop in Central Sulawesi - Masrianih Masrianih; I Made Budiarsa; Fatmah Dhafir; Manap Trianto (Jurnal Biologi Tropis, 2023)
Xylocopa latipes Drury are one species of bee found in the Hymenoptera order, in the family Anthophoridae. Carpenter bees, which are essential for plant pollination, build their nests in decaying wood and bark. Carpenter bees visit the bean crop to collect pollen and nectar for their hives. This study aims to determine the visit of the wood bee X. latipes on long bean plants in Central Sulawesi. The study employed a descriptive survey methodology that involved field sampling at bean planting and direct observation of X. latipes in the field. measured the temperature and the light intensity. The findings revealed that X. latipes visits to the bean crop at Desa Nambaru, Kecamatan Parigi Selatan, Kabupaten Parigi Moutong average 58,3 people each visit. The morning at 08.30 am averages 21 X. latipes visits; the afternoon at 15.30 pm averages 9 Xylocopa latipe visits; and the afternoon at 11.30 am averages 2 Xylocopa latipe visits. The amount of light present during X. latipes visit to the bean crop has a significant impact. Weather variables like temperature, humidity, and wind speed had an impact on the multivariate regression's very real relationship to X. latipes visit to bean planting.